Pengaruh Penggunaan Media Audio Visual Terhadap Motivasi dan Hasil Belajar IPA Siswa Kelas V SD Negeri Bontoramba - Dian Angreini; Muhiddin Muhiddin; Nurlina Nurlina (Universitas Muhammadiyah Enrekang, 2020)
This study is based on low motivation and learning outcomes learners because one of all factor is using and election the media less appropriate learning. So the researchers conducted experimental learning by using audio visual learning media. Formulation of problem in this research are Is there any effect of using audio visual media on motivation and learning outcomes of 5 th grade students at Bontoramba pallangga primary school? The purpose of this study is To explain effect of using audio visual media on motivation and learning outcomes of 5 th grade students at Bontoramba pallangga primary school. The research approach used is quantitative with the kind of quasi-experiment research. The sampling technique uses purposive sampling. The study population was all students of class V in Pallangga, sample taken are students of class V-A and V-B SD Negeri Bontoramba, Pallangga. Technique of collecting data using questionnaires, and tests. Data analysis techniques used is the Manova Test, which previously tested the prerequisite of normality and homogenity. The results showed that Manova test results questionnaire motivation and post test obtained Sig value. of 0.000. 0.000 < 0.05 then rejected and accepted, meaning there is effect of using audio visual media on motivation and learning outcomes of 5 th grade students at bontoramba pallangga primary school. So, it can be concluded that research audio visual media have the influence to motivation and learning outcomes of students. Keywords: Audio Visual Media, Learning Motivation, Learning Outcomes.